THE INFLUENCE OF DEPTH BEAM TO BENDING AND SHEAR CAPACITY ON SIMPLE BEAM - Samuel Layang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The purpose of this research is to find out the influence of depth beam to bending and shear capacity on simple beam. This research is using single span with length 6 m as a model.The width of the beam is constant (20 cm) and the depth of the beam have variation from 30 cm, 35 cm and 40 cm respectively.The load acting on the beamis selfweight, concentrated force and combination between selfweight and concentrated forced. The result of this research has showed that increasing of depth of beam will increase the bending and shear capacity. For the beamsthatonly account upon selfweight, increasing the depth ofbeam by 5 cm and 10 cm will increase the value of bending capacity 16.30% and 32.92% respectively. The beam thatonly accounts upon concentrated force, increasing the depth of beam by 5 cm and 10 cm will increasethe value of bending capacity36.11% and 77.78% respectively. The beamsthataccount upon selfweight and concentrated force, increasing the depth of beam by 5 cm and 10 cm will increase the value of bending capacity30.78% and 64.37% respectively. The beamsthat only account upon selfweight have the same shear capacity for all type of beam. The beamswhich only account upon concentrated force, increasing the depth of beam by 5 cm and 10 cm will increase the shear capacity value16.58% and 33.24% respectively. The beamsthat account upon selfweight and concentrated force, increasing the depth of beam by 5 cm and 10 cm will increase the value of shear capacity 11.08% and 21.12% respectively.